2015
DOI: 10.1016/j.jphs.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin alleviated myocardial remodeling of the left ventricle and improved cardiac diastolic dysfunction in diabetic rats

Abstract: Sitagliptin might have a myocardial protective effect by inhibiting apoptosis, inflammation, lipid accumulation and myocardial fibrosis in diabetic rats, for a potential role in improving left-ventricular function in diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 32 publications
4
23
0
Order By: Relevance
“…This is in concurrence with previous studies (Zhong et al 2006;Miao et al 2007;Van Linthout et al 2007;Wang et al 2009;Liu et al 2015). Fibrosis, which characterizes DCM, occurs independent of HTN or CAD and may be associated with myocardial hypertrophy (Huang et al 2010;Tarquini et al 2011).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is in concurrence with previous studies (Zhong et al 2006;Miao et al 2007;Van Linthout et al 2007;Wang et al 2009;Liu et al 2015). Fibrosis, which characterizes DCM, occurs independent of HTN or CAD and may be associated with myocardial hypertrophy (Huang et al 2010;Tarquini et al 2011).…”
Section: Discussionsupporting
confidence: 90%
“…Caspase-3 expression is increased by hyperglycemia-induced myocardial injury (Cai et al 2002), pressure overload-induced LVD (Philipp et al 2004), and in failing hearts (Narula et al 1999;Scheubel et al 2002) where it can induce myofibrillar ultrastructural damage (Condorelli et al 2001). A recent study conducted by Liu et al (2015) has demonstrated that DM upregulates receptor-interacting protein-3 (RIP 3 ), a signal molecule involved in TNF-a-mediated apoptosis. On the other hand, suppression of cardiac apoptosis is reported to improve the cardiac structure and function (Xie et al 2011;Zou and Xie 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable evidence also links the attenuation of DPP4 activity to improvement in ventricular function and reduced systemic and cardiac inflammation (6,(27)(28)(29). Hence, we were surprised to detect increased cardiac expression of mRNA transcripts encoding multiple effectors of the immune response in normoglycemic mice with reduced DPP4 activity.…”
Section: Discussionmentioning
confidence: 95%
“…1,2,5 Various animal models have been used in the study of LVDD, including the mRen2.Lewis rats, 9,10 deoxycorticosterone acetate-hypertensive rats, 30 spontaneously hypertensive rats (SHR), 31 streptozotocin and a high-fat diet-induced diabetic rats and mice, 32,33 lipopolysaccharide-induced high inflammation and LVDD, 34 and aortocaval fistula-induced volume overload model. 35 However, all these animal models are pathological models and may not reflect the biological conditions of LVDD that exist in healthy, aging women after the cessation of ovarian estrogen production.…”
Section: Discussionmentioning
confidence: 99%